Learning to hide : the English learning classroom as sanctuary and trap - Gray, Tricia Hagen (Education policy in practice., 2024)
"Just inside the school doors from the back parking lot, in the farthest reaches from the school entrance, there is a short corridor that leads to the hallway that houses Washington River High School's two English Learning classrooms. These classrooms offer both safe sanctuary for the school's growing population of Latinx students and a troublingly hidden space that allows most of the school and community to maintain the pretense of the generally prosperous, White, neighbor-helping-neighbor place of their myopic nostalgia. This Mayberry-like imaginary excludes the divisive sociopolitical battles of the last decade that have earned Washington River both local and national attention for a city ordinance that would fine landlords who rented to undocumented residents, a de jure policy that became de facto racial profiling. The English Learning classrooms are thus sites for the work of learning English and other academic subjects alongside the more abstract but no less important work of constructing citizen identities. In these spaces, adolescent Latinx newcomers negotiate and assert complicated claims about how they get to be of Washington River High School, the wider community of Washington River, and of the United States. As established residents and newcomers interact with each other (or not) in Washington River, they confront people who are linguistically, culturally, racially, and socially different from themselves. The polarized and contentious sociopolitical context of the United States in the wake of Donald Trump's election to the United States presidency in 2016 provides the backdrop to this nine-chapter book. The book centers the experiences of newcomer students as they construct citizen identities within the micro-context of their classroom and school and the macro-context of a changing and polarized United States. While this is an account of the local context of Washington River, the issues raised-welcome, unwelcome, belonging, and claiming rights-are not particular to Washington River. As part of the changing sociocultural landscape of the Midwestern United States, in which historically distinct groups come together in common spaces, Washington River High School offers an example of the concurrently familiar and uncomfortable ways that new receiving communities in the New Latino Diaspora (Hamann & Harklau, 2015; Hamann, Wortham, & Murillo, 2002) "host newcomers" (Lamphere, et al., 1992) within the common and complex institution of high school"--